2017
DOI: 10.1108/hcs-03-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes-based commissioning for social care in extra care housing: is there a future?

Abstract: IntroductionThis paper outlines the recent history of strategic and operational commissioning in England followed by a section on outcomes-based commissioning and its relevance for the planning and delivery of care and support to residents in extra care housing. An overview of a changing worldAs experienced practitioners will be fully aware, there have over the last 25 years been dramatic changes to the role of commissioners of adult social care. Following the NHS and Community Care Act 1990, the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…It is also important to recognise that the broader health and social care context within which ECH sites has changed dramatically since it first emerged. Smith et al. (2017), for example, have drawn attention to some of the complex challenges faced by those commissioning adult social care for residents in ECH, highlighting the central importance of reduced funding, meeting only higher eligibility criteria, increasing costs as a result of demographic change and the introduction of the national living wage (a mandatory pay rate for workers aged 25 and over).…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to recognise that the broader health and social care context within which ECH sites has changed dramatically since it first emerged. Smith et al. (2017), for example, have drawn attention to some of the complex challenges faced by those commissioning adult social care for residents in ECH, highlighting the central importance of reduced funding, meeting only higher eligibility criteria, increasing costs as a result of demographic change and the introduction of the national living wage (a mandatory pay rate for workers aged 25 and over).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, with the intention to provide a more personalised service with a more flexible response to need, service users and their carers have the opportunity to take more control in the planning and organisation of their own via self‐direct support and personal budgets. This has the potential to increase the complexity of commissioning at the operational level . However, it has been suggested that, particularly for older people with dementia, there will be a preference to minimise their responsibility in decisions regarding the purchasing of services and equipment and the creation of complex care packages .…”
Section: Discussionmentioning
confidence: 99%
“…For residents at Sites A, B and C, the move into ECH was therefore more likely to be a reactive one in which they were given less choice. This reaffirms that there is a disparity of experiences between older people who are tenants living in ECH schemes which act as providers of social housing and older people who are able to actively choose to become outright owners of apartments in luxury ECH schemes (Smith et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%